Assessment of Oral and Periodontal Health Literacy among Medical Students and Faculty: A Cross-sectional Study - Tabassum .; Anil Kumar; Renu Singh; Rajesh Kumar Thakur; Bipin Kumar Yadav (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Oral and periodontal diseases are highly prevalent and contribute substantially to systemic inflammation, impaired daily functioning, and reduced quality of life. Because oral health is closely interconnected with general health, medical practitioners play a crucial role in early detection, initial management, and timely referral of dental and periodontal conditions. Aim: To evaluate the knowledge, awareness, and attitudes regarding oral and periodontal health among undergraduate and postgraduate medical students and teaching faculty members. Materials and Methods: This cross-sectional questionnairebased study was conducted in the Department of Periodontology at the UPUMS, Saifai, Etawah, Uttar Pradesh, India, from January 2023 to June 2023. The sample size calculated was 1000, out of which 992 completed the questionnaire. Medical students and faculty were included, which were further categorised into three groups: undergraduate medical students (Group I), postgraduate medical students (Group II), and medical faculty members with senior residents (Group III). A structured, pretested and validated closed-ended 20 questionnaire assessed knowledge (Q1-5), awareness (Q6-14), and attitudes (Q15-20) toward oral and periodontal health. Demographic parameters such as age, gender, and level of education were recorded and considered during analysis. Data were analysed using Statistical Package for Social Sciences (SPSS) version 21.0, and group comparisons were made using the Chi-square test (p